0653 Poor sleep quality is associated with burnout in emergency medicine healthcare workers. (25th May 2022) - Norful, Allison; Belloir, Joseph; Firew, Tsion; Miranda, Maody; Shaw, Kaitlin; Schwartz, Joseph; Macron, Kathryn; Schultebraucks, Katharina; Sullivan, Alexandra; Chang, Bernard; Shechter, Ari
Abstract: Introduction: Prolonged exposure to stressful environments is associated with adverse psychological outcomes, including sleep disturbance and burnout. Burnout rates have increased substantially during the unprecedented challenges faced by healthcare workers (HCWs) during the COVID-19 pandemic. Since burnout has been associated with significant health risk and adverse organizational outcomes, it is important to identify factors that inform preventive or therapeutic approaches to mitigate adverse outcomes in HCWs. Methods: Participants were HCWs (physicians, nurses, advanced practice providers, technicians etc.) from 4 emergency departments in New York City who completed a cross-sectional electronic survey (completed at study enrollment between November 2020-October 2021). The Pittsburgh Sleep Quality Index (PSQI) assessed global sleep quality. The Maslach Burnout Inventory (MBI) assessed 3 burnout dimensions: emotional exhaustion (EE; feelings of being emotionally overextended and exhausted by one's work); Feelings of depersonalization (DP; unfeeling and impersonal response towards patients); and reduced personal accomplishment (PA; feelings of competence and successful achievement in one's work). Descriptive statistics were calculated and separate binary logistic regressions were used to predict poor global sleep quality (PSQI >5) from individual MBI subscales (dimensions of burnout), while controlling for age, race, ethnicity, and gender. Results: Ninety-one participants, studied to date, were included in the analysis (51% non-Hispanic/Latino White, 63% female, mean age: 40 [SD: 9.6] y). Poor global sleep quality was reported by 68%. High EE (score >9), DP (score >6) and reduced PA (score <9) were reported by 44%, 27%, and 18% of participants, respectively. Poor global sleep quality was significantly associated with presence of elevated EE (OR: 3.04, 95% CI: 1.07-8.63, p=0.037), but not with elevated DP (OR: 1.35, 95% CI: 0.44-4.10, p=0.603) or reduced PA (OR: 3.29, 95% CI: 0.65-16.44, p=0.146). Conclusion: During the COVID-19 pandemic, poor sleep quality was reported by the majority of participants and associated with increased burnout in HCWs. Poor global sleep appears to have the most influence on the burnout dimension EE, thus suggesting new evidence about associations between sleep and emotional regulation in HCW during the pandemic. Future trials should test whether existing (or novel) interventions can improve sleep and thereby support HCWs in high stress periods. Support (If Any): R01HL146911